Ganti Rugi dan Denda bagi Nasabah Pengemplang di Perbankan Syari’ah dalam Tinjauan Fikih Mu’amalat - M. Arif Al Kausari arif (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2023)
Compensation and fines for customers who violate are instruments used by Islamic banks to minimize the various risks that will be faced. This policy is based on three legal umbrellas, namely Bank Indonesia Regulation Number 11/25/PBI/2009, Fatwa of DSN number 43/DSN-MUI/VIII/2004 concerning Ta'widh and Fatwa of DSN number 17/DSN-MUI/IX/2000. Theoretically, the imposition of these fines has the potential to give birth to usury, even exactly with the usury model practiced by the ignorant community in the past, namely the debtor must pay more if he is in arrears in paying his debt to the creditor. This is contrary to the spirit of establishing Islamic banks as a way out of usury practices found in conventional banks. This study aims to analyze normatively-juridically regarding the arguments put forward by the DSN-MUI in issuing fatwas regarding fines and compensation for pemelang customers. This type of research is descriptive-analytic with a doctrinal approach, which refers to the arguments of Islamic jurists. The data collection technique used was literature documentation, using the DSN-MUI fatwa as the primary data source and the opinions of Islamic jurists as a secondary source. This study found that the DSN-MUI fatwa policy was based on the principle of benefit and prevention of harm in the form of customer moral hazard actions and safeguarding third party funds. This fatwa reconstructs the concept of compensation and fines as ta'zir for people who commit acts against the law.